When one is not enough: prevalence and characteristics of homes not adequately protected by smoke alarms. Issue 6 (2nd December 2005) - Peek-Asa, C; Allareddy, V; Yang, J; Taylor, C; Lundell, J; Zwerling, C
Abstract : Objective: The National Fire Protection Association (NFPA) has specific recommendations about the number, location, and type of smoke alarms that are needed to provide maximum protection for a household. No previous studies have examined whether or not homes are completely protected according to these guidelines. The authors describe the prevalence and home characteristics associated with compliance to recommendations for smoke alarm installation by the NFPA. Design, setting, and subjects: Data are from the baseline on-site survey of a randomized trial to measure smoke alarm effectiveness. The trial was housed in a longitudinal cohort study in a rural Iowa county. Of 1005 homes invited, 691 (68.8%) participated. Main outcome measures: Information about smoke alarm type, placement, and function, as well as home and occupant characteristics, was collected through an on-site household survey. Results: Although 86.0% of homes had at least one smoke alarm, only 22.3% of homes (approximately one in five) were adequately protected according to NFPA guidelines. Fourteen percent of homes had no functioning smoke alarms. More than half of the homes with smoke alarms did not have enough of them or had installed them incorrectly, and 42.4% of homes with alarms had at least one alarm that did not operate. Homes with at least one high school graduate were nearly four times more likely to be fully protected. Homes that had multiple levels, a basement, or were cluttered or poorly cleaned were significantly less likely to be fully protected. Conclusion: These findings indicate that consumers may not be knowledgeable about the number of alarms they need or how to properly install them. Occupants are also not adequately maintaining the alarms that are installed.